2003
DOI: 10.1007/s00192-004-1162-8
|View full text |Cite
|
Sign up to set email alerts
|

Suburethral tape via the obturator route: is the TOT a simplification of the TVT?

Abstract: Suburethral meshes can be implanted via the classic retropubic route (TVT) or by a new insertion technique that passes the tape into the obturator foramen (TOT). In a retrospective study we compared one 18-month period of 94 TOT (tension-free obturator tape) and one 18-month period of 99 TVT (tension-free vaginal tape), which preceded the change in the approach route. All operations were performed by the same surgeon using the same Prolene mesh and withno other surgical procedure associated. These two series w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
81
6
20

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 12 publications
10
81
6
20
Order By: Relevance
“…The results are not in agreement with the findings of other authors (9), where the majority of patients were discharged from the hospital on the first postoperative day.…”
Section: Discussioncontrasting
confidence: 99%
“…The results are not in agreement with the findings of other authors (9), where the majority of patients were discharged from the hospital on the first postoperative day.…”
Section: Discussioncontrasting
confidence: 99%
“…Ulmsten and Petros ¢rst introduced the TVT Neurourology and Urodynamics DOI 10.1002/nau Kuuva and Nilsson [2002] 1,455 patientsTVT 24/367 6 transfusion/signif bleed (0.4%), 11 bladder perforations (0.75%), 2 vascular injury (0.1%)1 nerve injury (0.07%), 4 abscesses (0.2%) Hong et al [2003] 375 patients, TVT 5/143 1 nerve injury (0.3%), 4 hematoma (1.1%) Kobashi and Govier [2003] 140 patients, SPARC 6/6 4 transfusions (2.8%), 1 bowel perforation (0.7%), 1 hematoma (0.7%) Karram et al [2003] 350 patients, TVT 6/97 2 hematoma (0.9%), 3 nerve injury (0.9%), 1urethral erosion (0.3%) Abouassaly et al [2004] 241 patients, TVT 7/173 6 signi¢cance bleed >500 ml (2.5%), 1 hematoma (0.4%) Levin et al [2004] 313 patients, TVT 2/67 2 unrecognized blad perf (0.6%) Wang [2004] 600 patients, TVT 0/28 Tsivian et al [2004] 200 patients, TVT 1/25 1 unrecognized blad perf (0.5%) Hodro¡ et al [2005] 445 patients, SPARC 2/82 1 bowel perforation (0.2%), 1 rectus hematoma (0.2%) Hammad et al [2005] 1,459 patients, TVT 993, SPARC 466 2/121 2 urethral erosion (0.1%) Paick et al [2005] 274 patients, TVT 0/110 De Leval [2003] 107 patients, TO generic (inside-out) 0/7 Delorme et al [2004] 32 patients, Uratape 0/8 DeTayrac et al [2004] 30 patients, Uratape 1/8 1 obturator hematoma (3%) Costa et al [2004] 183 patients, Uratape 2/20 2 urethral erosion (1%) Mellier et al [2004] 94 patients, Monarc 0/3 Domingo et al [2005] 65 patients, Uratape 43, Obtape 21 1/10 1 obturator abscess (1.5%) Fischer et al [2005] 220 patients, Monarc, Serasis-TO 0/18 Spinosa and Dubuis [2005] 117 patients, ObTape 0/10 Naidu et al [2005] 96 patients, Monarc 0/12 Siegel [2005] 30 patients, ObTape 1/6 1 obturator abscess (3%) Palma et al [2005] 100 patients, SAFYRE 0/20 Krauth et al [2005] 604 patients, I-STOP 1/60 1 signi¢cant bleed (0.2%) Davila et al [2005] 200 patients, Monarc 0/13 Roumeguere et al [2005] 120 patients, Uratape 60, Obtape 60 2/38 2 unrecognized urethra inj (1.7%)…”
Section: Discussionmentioning
confidence: 99%
“…Liapis et al 14 conducted a comparative study and concluded that the two routes are equally effective for surgical treatment of SUI, with cure rates of 90% and 89%, respectively. Mellier et al 15 conducted a similar study and observed cure rates of 90% for the retropubic approach and 95% for the transobturator approach. Similarly, Lee et al 16 reported a cure rate of 86.9% in both groups.…”
Section: Discussionmentioning
confidence: 89%